An Ambispective Observational Study on the Efficacy of Different Antithrombotic Therapies in Preventing Recurrent Cardiac Events in Patients with Myocardial Infarction - Mehta, Prince Manishkumar; Patel, Shivam Vikasbhai; Desai, Winnie Rakesh; Vyas, Ami (Indian Journal of Pharmacy Practice, 2026)
Background: Myocardial infarction remains a leading cause of cardiovascular morbidity and mortality in India. Antithrombotic therapy plays a crucial role in secondary prevention, yet comparative real-world data from Indian populations remain limited. Objectives: To compare the efficacy and safety of Dual Antiplatelet Therapy with Triple Antithrombotic Therapy in preventing recurrent cardiac events in post-myocardial infarction patients and evaluate the influence of demographics, comorbidities, and lifestyle factors. Materials and Methods: An ambispective, multi-centric, observational study enrolled 159 myocardial infarction patients (106 on Dual Antiplatelet Therapy, 53 on Triple Antithrombotic Therapy) across five hospitals in Gujarat, India. Efficacy was assessed by the Thrombolysis in Myocardial Infarction. Risk score (TIMI) and safety by the Bleeding Academic Research Consortium classification (BARC). Welch's t-test and Mann-Whitney U test were used for statistical comparisons. Results: Both therapies were predominantly prescribed to middle-aged males (50-69 years). Aspirin was universally used. Triple Antithrombotic Therapy patients had significantly higher baseline Thrombolysis in Myocardial Infarction scores (median 4.0 vs 2.0; p<0.0001). No bleeding events were recorded in either group. Diabetes significantly elevated risk scores in both groups. Hypertension was significant only in Dual Antiplatelet Therapy patients. Smoking was a statistically significant predictor of TIMI scores in both groups; its direction of effect in the DAPT group reflects the smoker’s paradox, while in TAPT, smokers had markedly higher risk scores. Conclusion: Both therapies demonstrated short-term safety. Diabetes and smoking are the most impactful independent risk factors, underscoring the need for individualized treatment and aggressive lifestyle modification post-myocardial infarction.
Keywords: Antithrombotic therapy; Bleeding Academic Research Consortium; Dual antiplatelet; therapy; Myocardial infarction; Recurrent cardiac events; Thrombolysis in Myocardial Infarction; score; Triple antithrombotic therapy